Asymmetry cointegration and the J-curve: New evidence from Malaysia-Singapore commodity trade - Bahmani-Oskooee, M.; Aftab, M.; Harvey, H. (Elsevier, 2016)
One previous research examined the short-run and the long-run effects of exchange rate changes on the Malaysian trade balance with each of its 11 largest partners using the linear and nonlinear ARDL models. No significant impact was discovered in the Malaysian model with its largest partner, Singapore. In this paper when we disaggregate their trade flows by 65 industries which conduct 91% of the trade, we discover the short-run asymmetric effects of exchange rate changes on the trade balance of almost all industries, adjustment asymmetry in 31 industries, short-run significant impact or cumulative asymmetric effect in 10 industries, and significant long-run asymmetric effects in 20 industries. The two largest industries, i.e., Petroleum and Electrical machinery with 40% share of trade were found to benefit from ringgit depreciation but not hurt by ringgit appreciation.